Serum chromium and selenium levels in type 2 diabetes mellitus - Eva, Hossneara; Akhter, Qazi Shamima; Alam, Md Khairul; Ahmed, Shahriar (Journal of Bangladesh Society of Physiologist, 2018)
Background: Emerging evidence suggests that several trace elements such as serum chromium (Cr) and selenium (Se) levels are altered in type 2 DM and its deficiencies are associated with the development of diabetes related complications. Objective: To assess the serum Cr and Se levels in patients of type 2 diabetes mellitus. Methods: This cross sectional study was conducted in the Department of Physiology, Dhaka Medical College, Dhaka from July 2014 to June 2015. Fifty type 2 diabetic patients with age ranging from 40 to 55 years were study group and fifty ages, BMI matched healthy subjects were control group. Patients were selected from Bangladesh Institute of Research for Diabetic Endocrine and Metabolic Disorders (BIRDEM) General Hospital, Dhaka. Serum Cr and Se levels were estimated by flame atomic absorption spectrophotometry. For statistical analysis unpaired Student’s‘t’ test and Chi square test were performed. Results: In this study, serum Cr and Se levels were significantly (P<0.001) lower in patients than that of control group. In addition 20% patients had low Cr and 16% had Se deficiencies. Moreover, 6% of control had low Cr and 4% had low Se. Conclusion: From this study, it is concluded that serum Cr and Se deficiencies are associated with type 2 diabetes mellitus. Bangladesh Soc Physiol. 2017, December; 12(2): 72-75